(untitled) (Bangladesh Medical Journal, 2014)
Global suicide rates have increased 60% in the past 45 years. Its incidence is also high in Bangladesh and the mode of suicide is hanging in majority of cases. This study summarizes the post mortem examinations on 334 cases of suicide by hanging during 2010 to 2012 in the Department of Forensic Medicine, Sir Salimullah Medical College and Mitford Hospital, Dhaka. The focus was on its epidemiology in Bangladesh and to identify factors that contributed to suicide. Among the 334 cases, 69.2% were male and 56.0% were married. Most (62.3%) were between 20 to 40 years. Most of the victims were from middle socioeconomic group. Regarding motive for committing the suicide by hanging, family disputes were most common motive (38.9%) in male and in female the most common motive was harassment particularly in married women (23.1%). The high incidence of suicidal hanging among young adults imposes a huge socioeconomic burden on our society. Private nature of hanging and easy availability of ligature materials and ligature points makes prevention of suicide by hanging a difficult task. Social, legal and psychiatric interventions are required to prevent suicide. DOI: http://dx.doi.org/10.3329/bmj.v43i2.21390 Bangladesh Med J. 2014 May; 43 (2): 90-93